(untitled) (American Journal of Arts and Human Science, 2023)
Human Immunodeficiency Virus (HIV) is an infectious disease leading to the top level of cause of died with high mortality and morbidity rates and requires relatively long diagnosis and therapy. HIV is a virus that attacks white blood cells (lymphocytes) in the body. which causes a decrease in human immunity, causing Acquired Immunodeficiency Syndrome (AIDS) (Dwi Astuti, 2022). In Indonesia, the number of positive HIV cases has been increasing yearly, and it mostly affects the productive age group, specifically individuals aged 25-49 years. HIV is a virus that weakens the human immune system. The occurrence of HIV is influenced by various factors contributing to its spread. This study aims to identify the risk factors associated with HIV incidence in Indonesia. The methodology involves a literature review, examining the risk factors for HIV incidence based on ten health journals published in the last ten years, following specific inclusion and exclusion criteria. Based on the reviewed journals, the risk factors for HIV incidence in Indonesia are as follows: male gender (OR=1.77), age <40 years (OR=7.25), first marriage at age <20 years (OR=5.62), married status (OR=2.54), a low education level (OR=4.70), common knowledge about HIV (OR=3.32), history of alcohol consumption (OR=7.65), history of using non-sterile needles (OR=3.42), history of family members with HIV/AIDS (OR=2.95), history of HIV-positive spouse (OR=83.74), history of sexually transmitted infections (STIs) (OR=2.92), heterosexual behavior (OR=3.15), homosexual behavior (OR=1.97), bisexual behavior (OR=2.08), engaging in combination sexual relationships (OR=4.89), having multiple sexual partners (OR=23.32), engaging in unprotected sexual intercourse (OR=5.34), and alternating injection drug use (OR=9.3). In the future, the Health Department needs to optimize health promotion methods among sex workers regarding condom use, provide HIV education for all age groups, and foster collaboration between HIV advocacy activists, non-governmental organizations (NGOs), healthcare professionals, and relevant institutions.